DETERMINANTS OF NET MARKETING INCOME OF DRY MAIZE (ZEA MAYS) IN ENUGU STATE, NIGERIA. - Uchechukwu, Ozor Maurice; Rita, Chiekezie Njideka; Annunciata, Isibor Chinwe; chijindu, Nwankwo Eucharia (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2024)
The study examined the determinant factors of net marketing income of dry maize (zea mays) in Enugu state of Nigeria. Specifically, it described profitability of dry maize marketing, determinant factors of net marketing income as wells as constraints faced by the dry maize marketers in the study area. Multistage, purposive and random sampling method were employed to select five (5) LGAs, (1) one market from each of the selected LGA, (10) ten wholesalers and (20) twenty retailers from the selected markets making a total of 150 respondents for the study. Enterprise Budgeting and Multiple regressions were the analytical tools employed. 4-point likert scale was used to find out the constraints faced by the marketers. Profitability indicators such as net marketing income, return on investment, net return on investment were N11,489,409.85, 1.5 and 0.5 for wholesalers of dry white maize N9,511,009.85, 1.6 and 0.6 for wholesalers of dry yellow maize; while N8,214,249.4, 1.6 and 0.6 were for retailers of dry white maize and N8,905,392.4, 1.8 and 0.8 for retailers of dry yellow maize respectively. These proved the business profitable. Socio –economic characteristics factors of the respondent’s especially marketing cost and product price statically and significantly influenced net marketing income realized by pooled wholesalers and retailers, wholesalers and retailers of white and yellow maize at each instance. Constraints to dry maize marketing were high cost of transportation, inadequate capital, storage pests and diseases, high market levy, unstable prices, poor storage facilities, too many traders, inadequate market information and poor sales. The dry maize marketers should form cooperative societies to enable them transact the business at minimal cost and earn higher profit.